A japán vállalatirányítás (corporate governance) átalakulása - Éva Ozsvald (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
– The pressures to accommodate to the global standards of corporate governance (CG) for Japanese public companies had grown strong since the mid-1990s. A series of legal reforms has led to the formal imitation of the market oriented Anglo-American model which, however, was not accompanied by the functional convergence of the CG practices of the Japanese companies. Deeply rooted social norms, insider business culture and industry specific conditions had a strong effect on the course of CG reforms in Japan. A hybrid model of corporate governance has been emerging in which companies selectively combine the features of the traditional stakeholder based approach with those of the shareholder oriented system.
Keywords: G34; P50; 330; Japan; corporate governance; shareholder value; Corporate Governance; Shareholder Value; Japan